Penerapan Cooperative Integrated Reading Composition (CIRC) dalam Pembelajaran Menulis Ringkasan Dongeng Berbahasa Prancis - Iis Sopiawati; Yadi Mulyadi (Jurnal Pendidikan Bahasa dan Sastra, 2023)
Writing a fairytale summary is one of the writing skills required in French writing competency level B1 DELF. To acquire this competence requires a lot of practice. The selection of appropriate learning models that can be used in writing summaries of fairytales must be adapted to the learning objectives to be achieved. This study aims to (1) describe the stages and the results of students' ability to write a summary of French fairytales during the implementation of Cooperative Integrated Reading Composition (CIRC) in learning to write a summary of French fairytales, and to evaluate the effectiveness of CIRC implementation. The method used in this research is the pre-experimental method using the one-group pretest-posttest research design and the research instrument is a test. The results that have been achieved in this study, namely the average student pre-test score was 76, while the post-test average score was 84.3, so there was an increase in score of 8.3. From the results of statistical calculations showed that the t-count value is 5.50 and the t-table value is 2.09, so that with a significance level of 5% and 19 degrees of freedom, so the working hypothesis in this study is accepted. It means that the application of CIRC is effective in learning to write a summary of fairy tales in French. Thus, through this research, students can better understand the fundamental rules and stages in writing a summary of a fairy tale in French.